Pengaruh High Performance Work System (HPWS) dan Konflik Peran terhadap Kepuasan Kerja - Alifa Nur Maulidina; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The purpose of this research is to study the impact of the High-Performance Work System (HPWS) and role conflict on job satisfaction at PT Temprina Media Grafika, Nganjuk Branch. The sampling technique used was non-probability sampling”this study uses questionnaires distributed to 40 office employees who worked at PT Temprina Media Grafika Nganjuk. The statistical analysis used in this study was multiple linear tests using SPSS. The results of data testing indicate that HPWS has a significant positive relationship with job satisfaction. This shows that the practice of HPWS in the company is going well, and the level of perceived job satisfaction has also increased. As well as role conflict has a significant negative relationship with job satisfaction. The data test results show that role conflicts that occur within the company will result in a decrease in job satisfaction felt by employees.